Students' Perceptions of Islamic Religious Education Teachers' Exemplary - Ruswandi, Agus (LETIGES, 2025)
This study aimed to examine students' perceptions of Islamic Education teachers' exemplary behaviour (Uswah Hasanah) and its influence on students' moral and behavioural tendencies in a vocational school context. Using a quantitative survey design, data were collected from 106 students of SMK As Sulaimaniyyah, Cianjur, Indonesia, through a structured questionnaire developed based on Islamic pedagogical frameworks and ethical teacher behaviour indicators. The instrument demonstrated high reliability (Cronbach's Alpha = 0.87). Data were analysed using descriptive and inferential statistics through SPSS version 2.5, including mean scores, t-tests, one-way ANOVA, and Pearson correlation. The results revealed that students' overall perceptions of their teachers' exemplary behaviour were very high (M = 4.61), with the indicator of teachers’ influence on students obtaining the highest mean (M = 4.83), followed by religious devotion, patience, humility, and discipline. At the same time, asceticism was rated as the lowest (M = 4.17). Significant differences were found based on gender (t = 2.97, p < 0.05), frequency of interaction (F = 3.41, p < 0.05), and academic achievement (F = 2.103, p < 0.05). These findings affirm that teacher exemplarity plays a critical role in shaping students’ moral awareness and conduct, particularly in vocational schools where religious exposure is limited. The study recommends integrating continuous professional development and reflective ethical training for Islamic Education teachers to strengthen their role as moral exemplars in the digital era.